A review of high temperature (≥ 500 °C) latent heat thermal energy storage. (May 2022) - Opolot, Michael; Zhao, Chunrong; Liu, Ming; Mancin, Simone; Bruno, Frank; Hooman, Kamel
Abstract: Demand for high temperature storage is on a high rise, particularly with the advancement of circular economy as a solution to reduce global warming effects. Thermal energy storage can be used in concentrated solar power plants, waste heat recovery and conventional power plants to improve the thermal efficiency. Latent thermal energy storage systems using phase change materials are highly thought for such applications due to their high energy density as compared to their sensible heat counterparts. This review, therefore, gives a summary of major factors that need to be assessed before an integration of the latent thermal energy system is undertaken. In addition, challenges faced when constructing and experimenting with the storage systems are mentioned. Finally, an insight on the cost analysis and the general performance metrics of the latent thermal energy storage systems is provided before conclusions are drawn. Highlights: High temperature phase change materials for CSP thermal energy storage. Phase change materials in CSP plants. Challenges in building LTES systems. TES sizing and effectiveness.